World War II and two occupations : dilemmas of Polish memory - Wolff-Powęska, Anna 1941- HerausgeberIn; Forecki, Piotr 1978- HerausgeberIn; Skowrońska, Marta ÜbersetzerIn; Zahorjanova, Blanka ÜbersetzerIn (Geschichte - Erinnerung - Politik, 2016)
"This anthology presents the work of several authors from different academic disciplines. Film and literature experts, sociologists, historians and theatrologists analyse the Polish memory of the Nazi and Stalinist occupations, which are key components of Polish collective identity. Before the political turn of 1989, the memory of World War II was strictly controlled by the state. The elements of memory related to the Soviet occupation were eradicated, as well as any other elements that did not fit the official narrative about the war. Unblocking the hitherto limited public discourse resulted in the process of filling the blank pages of history and the development of different and frequently conflicting communities of memory"--Provided by publisher